Engaging with perpetrators of intimate partner violence : an exploration of inter-agency collaboration in the Western Cape - Padayachee, Venessa Claudette Thigesharee (Institute of Criminology, 2015)
The prevalence of violence between intimate partners in South Africa is widely acknowledged. Social and legal reforms have attempted to address the needs of victims of intimate partner violence. This study drew on social learning theory to explicate the causative factors involved in intimate partner violence. According to international best practices, treatment interventions for batterers are based on psycho-educational and cognitive behavioural principles and provided in community-based group settings. Coordinated community responses are likely to provide favourable outcomes for batterer intervention and the prevention of intimate partner violence. Key features of batterer intervention programmes and issues that affect their efficacy are outlined.